Relational Group Analysis. A Response to R. Billow: Relational Group Psychotherapy: An Overview: Part II: Relational Models of Group Process, June 2017. (June 2017) - Berman, Avi
The simultaneous existence and evolvement of the intra-psychic and the interpersonal is the basis of the term 'relational'. Group analysis seems to have the same convictions about the essence of the human mind, the interconnection of minds and the need to refresh our psychotherapeutic concepts. Referring to Billow's article, I suggest that the clearest connection between his ideas, the relational point of view and group analysis is his view about the meaning of nodes as an active (rather than passive) processing communication. However, contemporary relational thinking requires some self-report of the therapist's counter-transference as a manifestation of relational attitude. From this point of view, some parts of Billow's article are written from an orthodox, one-person psychology perspective. It seems that Foulkes' suggestion that the conductor is also a participant and is subject to the same group processes is an essential connection between group analysis and relational thinking. Recognizing and understanding the conductor's participation in the group may be relevant and rewarding to our professional elaboration in relational terms.